The role of affective commitment in higher education student loyalty - Ccorisapra-Quintana, Jeferson (2022)
The purpose of this paper is to examine the effect of affective commitment on the loyalty of higher education students. The student population involved corresponds to a total of 2029 students belonging to three faculties and enrolled in the 2021-II academic semester of a public university in the province of Andahuaylas, Apurimac region, of which, data were collected from 271 students equivalent to 13.36 % of the population. The quantitative route, cross-sectional design and explanatory level were followed. Two existing validated constructs were used to measure students' perceptions through a virtual questionnaire. To find cause-effect, simple linear regression of SPSS 27 statistic was used. The result of the inferential statistics found that affective commitment positively and significantly influences students' loyalty at a moderate level (R2 = 0.588***). The findings infer that the emotional bond generated by students with the university increases their levels of loyalty, identification and feelings of permanence.